Mineralogy and sulfide mineral chemistry of Khabr iron ore, Southwest of Baft (Southeast of Sanandaj-Sirjan Zone) - Mohammad Boomeri; Habib Biabangard; Somayeh Dehghani Soltani; Azadeh Bordbar (پترولوژی)
Introduction The Khabr iron ore is located in about 55 km southwest of Baft and 15 km northeast of Khabr in the southeastern part of the Sanandaj-Sirjan zone. This zone hosts a large number of iron deposits of Iran such as Golegohar in Sirjan. The Khabr iron ore is a small and unknown deposit, mainly composed of supergene iron hydroxides outcrops. The Khabr iron ore is a hydrothermal mineralization that has occurred in marble during primary and secondary stages as oxide and sulfide (Dehghani Soltani, 2012). There is rare information about mineralogy, paragenesis and genesis of the study deposit This paper aims to study the mineralogy of hypogene and supergene ores and the chemistry of sulfide minerals. Material and Methods Following field study and sampling from the rock units, alteration zones, iron ore and sulfide veins, 45 thin sections and 12 polished sections were prepared and studied by transmission and reflective light microscopes at the University of Sistan and Baluchestan and X-ray diffractometry (XRD) at the Yamagata University. The sulfide minerals are analyzed by the Electron Probe Micro Analyze (EPMA) model of JEOL. JXA-8600 with an accelerator voltage of 15kv and current of 2×10-8 A in Yamagata University. Geology The oldest rocks in the Sanandaj-Sirjan zone are metamorphic rocks of the late Precambrian-Cambrian period (Ghorbani, 2008), In this zone, Paleozoic and Mesozoic rocks such as carbonate, quartzite, and volcanic rocks with layers of shale and sandstone are covered by Hamedan phyllites (Ghorbani, 2008). The Cretaceous rocks in this zone are mainly carbonated rocks and ophiolitic complex. The Tertiary outcrops in the Sanandaj-Sirjan zone are relatively small. Several intrusive bodies in the Sanandaj-Sirjan zone were formed in the Middle and Late Triassic, Late Jurassic, Late Cretaceous and Paleocene periods. They are mainly intermediate to acidic in composition (Ghorbani, 2008). Most pre-Mesozoic rocks in the Sanandaj-Sirjan zone were metamorphosed. The metamorphic complexes in the study area are Golegohar, Rutchun and Khabr (Figure 1B). The Khabr Iron mineralization is located in the Rutchun complex, which is on top of the Golegohar complex (lower Cambrian) and below the Khabr complex (Devonian) (Figure 1B). The host rock units in this area are an alternation of carbonate rocks, phyllite, greenschist, mica schist and quartz-schist ranging in age from Upper Cambrian to Ordovician. The dominant minerals in these rock units are calcite, quartz, biotite and muscovite including sericite, paragonite, chlorite and clay minerals. Discussion and Results The iron mineralization occurs at the contact of carbonate rocks and phyllite and schists. The mineralization develops in a northeast-southwest orientation as hill-like and isolated outcrops including hypogene oxide and sulfide mineralization and supergene iron oxide mineralization. The hypogene iron mineralization is characterized by magnetite euhedral crystals, formed as replacements in carbonate rocks by hydrothermal solutions. The hypogene sulfide mineralization forms following the oxide mineralization as silica veins, cavities and open space filling. Sulfides are associated with quartz and composed of pyrite, arsenopyrite, chalcopyrite, bornite and covellite. The chemistry of arsenopyrite, pyrite and chalcopyrite contain low volumes of gold, silver, bismuth, Pb, Zn, Te and mercury. Some pyrite grains contain Au (maximum 700 ppm) (Table 2). The iron ore outcrops are mainly supergene-type formed as open space filling in fractures or around gangue grains boundary. The supergene iron mineralization is due to the weathering of hypogene minerals such as magnetite and sulfide minerals. The margin of the outcrops of the sulfide veins are partially altered to iron hydroxides in brown, red and yellow. The supergene ore minerals are mainly goethite, hematite and limonite. Calcite, dolomite, quartz and phyllosilicates are the predominant gangue minerals. There exist many secondary structures in iron ore like grape-like, colloidal, box-like, cavity-like, rhythmic, replacement and vein-like and open space filling all are indication of weathering and supergene processes. Some textures of the host rocks are similar to clastic rocks like the magnetite-rich sandstone. The magnetite texture reveals that, the Khabr hypogene iron mineralization is mainly formed as a replacement in carbonated rocks by hydrothermal solutions. High temperature acidic hydrothermal solutions containing chloride complexes, dissolve the carbonate rocks upon reaction with them (Robb, 2005). By dissolving carbonate rocks and increasing the pH, chloride complexes became unstable and magnetite replaced limestone. The Khabr sulfides mineralization in the quartz veins is more characteristic of hydrothermal solutions. The hydrothermal solutions containing metal-sulfide complexes had migrated along faults and permeable zones and then with a decrease in the temperature and pressure, the sulfides had been formed. The fluids responsible for the Khabr sulfide stage have the same salinity and temperature as of the those of epithermal deposits (Dehghani Soltani, 2012). The formation mechanism of supergene mineralization is well-known (Guibert and Park, 1986). The Khabr supergene iron ores are the result of magnetite and sulfide oxidation to goethite, hematite and limonite. The magnetites replaced in limestone and marble and magnetites in clastic sandstone have been weathered and altered by oxygen- and carbon dioxide-rich surface waters. The mineralization zone is severely faulted, crushed and permeable. As a result, the circulation of the oxygen-rich waters toward depths or decomposition of magnetite and sulfides had been possible. Conclusions The Khabr Fe mineralization can be divided into hypogene and supergene stages. The hypogene stage can be divided into sub-stages of oxide and sulfide mineralization. The hypogene oxide stage is characterized by magnetite, formed as a replacement in limestone by hydrothermal solution or as clastic grains in sandstone. The remarkable features of the hypogene sulfide stage are the presence of arsenopyrite, pyrite and chalcopyrite in quartz veinlets precipitated from hydrothermal solutions like those of epithermal type. The supergene mineralization is characterized by iron oxides and hydroxides as hematite, goethite and limonite precipitated from surface waters. Acknowledgments We acknowledge Kazuo Nakashima professor of Yamagata University for his assistance with EPMA and XRD. We thank the reviewers who provided useful comments on an earlier draft of this paper.